Molecular expression of aquaporin mRNAs in the northern house mosquito, Culex pipiens. (January 2017) - Yang, Liu; Piermarini, Peter M.
Graphical abstract: Highlights: Our study characterizes AQP mRNA expression in the mosquito, Culex pipiens . AQP mRNAs were differentially expressed among life stages, but not between sexes. After a blood meal or hemolymph injection, AQP mRNAs were differentially expressed. After exposure to a low relative humidity, AQP mRNAs were down-regulated. Abstract: Aquaporins (AQPs) are a family of membrane-bound proteins, originally described as water-channels, that broadly exist in prokaryotic and eukaryotic cells. However, some AQPs can transport small molecules (e.g. urea, glycerol) along with or preferentially to water. Previous work in the mosquitoes Aedes aegypti and Anopheles gambiae have characterized the molecular expression of one or more AQP genes and shown that they are involved in water homeostasis after blood feeding, tolerance to dehydration and heat stresses, and development of Plasmodium falciparum in the mosquito. However, the molecular expression of AQPs in the northern house mosquito Culex pipiens, the primary vector of West Nile virus, is presently unknown. Here we characterize the relative mRNA expression of six AQP genes in C. pipiens . We used quantitative RT-PCR (qPCR) to compare AQP mRNA levels 1) among different life stages and sexes, 2) between blood fed and non-blood fed adult females, 3) between adult females injected with phosphate-buffered saline (PBS) and non-injected females, and 4) between adult females exposed to a low vs. high relative humidity. We found that: 1) four AQP mRNAs (Drip, Bib, Eglp1, Aqp12L) were differentially expressed between larval and adult life stages, but not between sexes; 2) after a blood meal, the expression of two AQP mRNAs (Drip and Aqp12L) were down-regulated and one AQP mRNA (Eglp2) was up-regulated; 3) the expression of two AQP mRNAs (Drip and Prip) were down-regulated and one AQP mRNA (Eglp1) was up regulated after injecting the hemolymph of mosquitoes with PBS; and 4) the expression of Prip and Eglp2 mRNAs were both down-regulated in response to a low relative humidity. Our study is the first to characterize the molecular expression patterns of AQPs in C. pipiens, thus providing a foundation for future research elucidating the physiological and functional roles of AQPs in this important disease vector.